Analysis of presenting complaint and co morbidity of the mortality at Patan Hospital Emergency Department - Bajracharya, Sumana (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Studies in mortality are important since they help to describe the quality of service in the particular department This study is aimed to know the various causes of mortality in emergency department and other associated factors. Method: It is a retrospective study data will be collected from the charts of mortality patients in emergency department in the year 2067 BS. The relation of death in emergency department (ED) with time, duration of stay, age, sex and their primary diagnosis was observed. We will also determined. The cause of death and the underlying disease in these patients were also analyzed. Result: Among those who died, their most common chief complain on initial presenting complain had been shortness of breath (28.3%), followed by unresponsiveness (16.7%), altered sensorium (13.3%), poisoning (13.3%) and others. The leading underlying disease were Chronic obstructive pulmonary disease (COPD) (11.7%), head injury (11.7%), pneumonia (11.7%), aluminium phosphide poisoning (10%) and acute coronary syndrome (ACS) (8.3%). There were various causes of death found among which commonest one being respiratory failure(30%),followed by raised ICP (11.7%) septic shock (11.7%), heart failure (8.3%), hypovolemic shock (8.3%). Most of the patient died within 6 hours of hospital entry (n=43). 10 patients died within 6 to 12 hours and 7 patients died after 12 hours. Conclusion: This study concludes that the most common cause of death in ED were COPD, aluminum poisoning, head injury, pneumonia and ACS.